A highly stretchable, easily processed and robust metal wire-containing woven fabric with strain-enhanced electromagnetic shielding effectiveness. Issue 17 (September 2021) - Wang, Yong; Gordon, Stuart; Yu, Weidong; Wang, Zongqian
Textiles that contain integrated conducting components are drawing attention for their ability to mitigate electromagnetic radiation pollution. Maintaining effective and robust electromagnetic shielding effectiveness (EMSE) under different modes, e.g. stretching, bending and washing, is of importance in protecting humans and information-sensitive electronic devices from exposure to electromagnetic interference. In this work, a weft-stretchable, conductive fabric (W-SCF) was specially manufactured for electromagnetic shielding characterization by integrating stainless steel filament (SSF) in the weft direction. The results demonstrate that our as-prepared W-SCF was effective for shielding purpose with its EMSE dependent on the orientation of the SSF within the fabric structure. Specular reflection caused by the close arrangement of the SSF and the lower electrical resistance of the fabric on per unit area basis were responsible for the enhanced shielding properties when the fabric was stretched. Furthermore, using the fabric in a 90°/90° laminated form improved the EMSE values compared with a single layer and a 0°/90° laminated versions. Importantly, the W-SCF exhibited resistance to 10 laundering cycles, 20 stretching cycles (at 25% extension), 50 bending cycles and 100 abrasion cycles, demonstrating its robustness and durability. This work is believed to take a new step in development of reliable and advance shielding materials for special protective application.